UPAYA PENINGKATAN KESELAMATAN PENERBANGAN MENGGUNAKAN INSTRUMENT LANDING SYSTEM (ILS) TERHADAP KELANCARAN PELAYANAN LALU LINTAS PENERBANGAN DI BANDAR UDARA DOMINE EDUARD OSOK SORONG - Maulana Pagawak; Julfansyah Margolang; Ariyono Setiawan (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Domine Eduard Osok (DEO) Sorong Airport is one of hub airports which have huge amount of flights in West Papua Province. Go around / missed approach due to unstabilized approach are frequently happened. Obviously, it gives an impact on the flights traffic. The purpose of this study is endeavoured to improve the safety of flight through the application of instrument landing system which would create the regularity of aircraft traffic more effective.This study use a descriptive qualitative method that use the document of ICAO, Directorate General of Civil Aviation Indonesia and scientific paper as the resources. Instrument of this study are Questionnaire and data from Airnav Sorong. The data are processed with the likert scale.This study shows that unstabilize approach is happened due to technical factor, weather and wind. The result shows 83% of respondents are agreed that the application of ILS would undertake the unstabilize approach. Therefore, it would increase the traffic flow of air traffic in Sorong Airport.